2021
DOI: 10.3390/ijms22020729
|View full text |Cite
|
Sign up to set email alerts
|

A Micellar Formulation of Quercetin Prevents Cisplatin Nephrotoxicity

Abstract: The antioxidant flavonoid quercetin has been shown to prevent nephrotoxicity in animal models and in a clinical study and is thus a very promising prophylactic candidate under development. Quercetin solubility is very low, which handicaps clinical application. The aim of this work was to study, in rats, the bioavailability and nephroprotective efficacy of a micellar formulation of Pluronic F127-encapsulated quercetin (P-quercetin), with improved hydrosolubility. Intraperitoneal administration of P-quercetin le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 65 publications
(43 reference statements)
1
19
0
Order By: Relevance
“…A few more examples of flavonoids, such as artocarpanone, artocarpin, cycloartocarpin, and cyanomaclurin, extracted from Artocarpus heterophyllus heartwoods have a synergistic effect with cisplatin on non-small lung and breast cancers [145]. Recent studies have shown that quercetin prevented cisplatin nephrotoxicity by ameliorating tubular damage [146]. Isoquercetin and rutin, flavonoids from Morus alba, have been shown to enhance the therapeutic efficacy of cisplatin significantly compared to a single dose of cisplatin alone in treating gastric cancer [147].…”
Section: Combination With Flavonoidsmentioning
confidence: 99%
“…A few more examples of flavonoids, such as artocarpanone, artocarpin, cycloartocarpin, and cyanomaclurin, extracted from Artocarpus heterophyllus heartwoods have a synergistic effect with cisplatin on non-small lung and breast cancers [145]. Recent studies have shown that quercetin prevented cisplatin nephrotoxicity by ameliorating tubular damage [146]. Isoquercetin and rutin, flavonoids from Morus alba, have been shown to enhance the therapeutic efficacy of cisplatin significantly compared to a single dose of cisplatin alone in treating gastric cancer [147].…”
Section: Combination With Flavonoidsmentioning
confidence: 99%
“…Based on those results, quercetin 3-O-glucuronide could be responsible, at least in part, for the nephroprotective effect of quercetin against cisplatin damage observed in vivo [3,15]. Furthermore, the protective effect of the metabolite could explain our in vivo results regarding to the absence of protection of oral P-quercetin, when the same formulation has previously been shown to be effective intraperitoneally [16]. The differences observed between the administration of P-quercetin by the intraperitoneal and oral vias cannot be explained by its absorption, since it seems to be very similar for both routes.…”
Section: Discussionmentioning
confidence: 55%
“…In our in vivo model, renal function was heavily damaged by cisplatin. However, this effect was not ameliorated by oral P-quercetin, as was the case with intraperitoneal administration of the formulation in our previous experiments [16]. Rats in the cisplatin (CP) group experienced an acute kidney injury (AKI), as they showed a progressive increase in their plasma creatinine (Crpl) and urea levels compared to those of the controls (Figure 1a).…”
Section: Nephroprotection Study With Oral P-quercetinmentioning
confidence: 78%
See 1 more Smart Citation
“…The possibility of clarifying these aspects would allow us to establish strategies such as the encapsulation of an active metabolite to favor its accumulation in the kidney. In our laboratory, it has been shown that the encapsulation of quercetin with Pluronic F127 enhances the biopharmaceutical properties, increases the bioavailability of the flavonoid, and maintains the renoprotective properties against quercetin aglycone [74]. Similarly, the encapsulation of the active metabolite would facilitate its access to the tubular cell, its renal metabolism, and its accumulation.…”
Section: Aspects To Be Elucidated and Limitations Of Current Studiesmentioning
confidence: 99%